Analysis of the nexus between population, water resources and Global Food Security highlights significance of governance and research investments and policy priorities - Yunusa, I.; Zerihun, Ayalsew; Gibberd, Mark (John Wiley and Sons Inc., 2018)
BACKGROUND: Analyses of sensitivity of Global Food Security (GFS) score to a key set of supply or demand factors often suggest population and water supply as being the most critical and on which policies tend to focus. To explore other policy options, we characterised the nexus between GFS and a set of supply or demand factors including defining including population, agricultural and industrial water-use, agricultural publications (as a surrogate for investment in agricultural research and development [R&D]), and corruption perception index (CPI), to reveal opportunities for attaining enduring GFS. RESULTS: We found that despite being the primary driver of demand for food, population showed no significant correlation with GFS scores. Similarly agricultural water-use was poorly correlated with GFS scores, except in countries where evaporation exceeds precipitation and irrigation is significant. However, GFS had a strong positive association with industrial water-use as a surrogate for overall industrialisation. Recent expansions in cultivated land area failed to yield concomitant improvements in GFS score since such expansions have been mostly into marginal lands with low productivity and also barely compensated for lands retired from cropping in several developed economies. However, GFS was positively associated with agricultural R&D investments, as it was with the CPI scores. The apparent and relative strengths of these drivers on GFS outcome amongst countries were in the order: industrial water-use ˜ publication rate ˜ corruption perception > agricultural water-use > population. CONCLUSIONS: We concluded by suggesting that to enshrine enduring food security, policies should prioritise (1) increased R&D investments that address farmer needs, and (2) governance mechanisms that promote accountability in both research and production value chains. This article is protected by copyright. All rights reserved.